Perilipin 5 alleviates ferroptosis of cardiomyocytes by targeting USP10-p53-TfR proteasome-dependent degradation - Jianqiao Zhao; Jiacheng Shui; Qiyao Xu; Xindong Wang; Yuehong Shen; Chengyuan Liu; Jianping Shen (Frontiers in Medicine)
IntroductionPerilipin 5 (PLIN5) is a key protein attached to lipid droplets that plays a critical role in cellular lipid metabolism. However, its involvement in cardiomyocyte ferroptosis has not been fully elucidated. This study explored the impact of PLIN5 on ferroptosis in H9c2 cells and a rat model of myocardial infarction (MI).MethodsH9c2 cells were treated with H2O2 and Erastin, while the rat model of MI was established by ligating the left anterior descending coronary artery.ResultsWe found that after MI, cardiac subcellular iron levels increased and the expression of PLIN5 decreased. Overexpression of PLIN5 reduced lipid peroxidation, enhanced ferroptosis resistance, decreased iron accumulation, and lowered TfR expression. Additionally, there was an interaction between PLIN5 and ubiquitin-specific peptidase 10 (USP10). PLIN5 increased the ubiquitination of p53. USP10 and MG-132 blocked the regulatory effect of PLIN5 on TfR expression. Overexpression of USP10 weakened the inhibitory effect of PLIN5 on ferroptosis. In vivo experiments showed that overexpression of PLIN5 significantly reduced ferroptosis in the infarcted myocardium.DiscussionPerilipin 5 may exert cardioprotective effects by regulating the USP10 and p53-TfR axis.